Pengaruh Gaya Kepemimpinan Demokratis, Beban Kerja dan Motivasi Instrinsik terhadap Prestasi Kerja Pegawai Dinas Lingkungan Hidup dan Kehutanan DIY - Kusuma Chandra Kirana; Epsilandri Septyarini; Ummi Nurmustofa (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpouse of this study was to the effect of democratic leadership style, workload and instrinsic motivation on the work performance of Dinas Lingkungan Hidup dan Kehutanan DIY employee. The population and samples used in this study were all employees of the Dinas Lingkungan Hidup dan Kehutanan DIY, totaling 90 people using the saturated sampling method. Methods of data collection using questionnaires. IBM SPSS Statistics 25 is used as data analysis trought two stages of testing, namely: classic assumption test and hypothesia test (t test and f test). The results of this study show that the leadership style is not effect on work performance. There is a positive and significant effect on workloard and instrinsic motivation variabels on employee work performance and democratic leadership style, workload and instinsic motivation affect employee performance in the Dinas Lingkungan Hidup dan Kehutanan DIY.